The use of molecular-genetic and phytopathological methods to identify genes for effective leaf rust resistance in Aegilops accessions - L. G. Tyryshkin; M. A. Kolesova (Труды по прикладной ботанике, генетике и селекции)
Background. Identification of effective genes for disease resistance in resistant plant samples is the most important step toward recommending them for breeding. There are three main methods for such identification: hybridological analysis, phytopathological test, and DNA marking. The method of PCR markers is widely used in Russia to identify resistance genes in wheat relatives, including the genus Aegilops L. for resistance to leaf rust. From a theoretical viewpoint, the presence of a certain amplification fragment can hardly be interpreted as a definite proof of the presence of a resistance gene: during the species evolution, recombinations and mutations could occur, resulting in disturbance of the fragment’s presence and phenotypic expression of its connection with resistance. The purpose of this work was a comparison between molecular-genetic and phytopathological methods to identify leaf rust resistance genes Lr9 and Lr41 in three Aegilops species.Materials and methods. We identified leaf rust resistance genes Lr9 and Lr41 in forty Aegilops accessions using PCR with J13 and GDM35 primers, respectively. In the phytopathological test, the seedlings were infected with the pathogen population (avirulent to Lr9 and Lr41 genes) and the fungus clones virulent to the wheat line with the Lr9 gene.Results and conclusions. According to the data of molecular marking, the Lr41 gene was present in twelve Ae. tauschii Coss. accessions; Lr9 in four Ae. umbellulata Zhuk. accessions and four of Ae. biuncialis Vis. All accessions of Ae. tauschii, two of Ae. umbellulata, and three of Ae. biuncialis, possessing effective resistance genes according to the molecular testing, were susceptible to the pathogen population. For three Ae. umbellulata accessions resistant to the population, where DNA marking failed to identify an Lr9 gene, the presence of this gene was shown by a phytopathological test. Thus, there were significant differences in the postulation of effective Lr9 and Lr41 leaf rust resistance genes in Aegilops accessions after a phytopatological test and the use of DNA markers.